The influence of selebgram as celebrity endorsement and product quality on purchase decisions moderated with brand image - Dheasey Amboningtyas; Leonardo Budi Hasiholan (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to determine the impact of Celebgram as celebrity endorsement and product quality on purchasing decisions mediated by brand image. The population and sample in this observation are Yogyakarta residents participating in Ella Skin Care. This observation was sampled using a non-probabilistic sampling technique. The analytical methods used in this study are instrumental tests consisting of validity and reliability tests, descriptive statistics tests, normality tests, multicollinearity tests, heterocystism tests and classical autocorrelation tests using SPPS. Hypothesis testing consisting of conservative hypothesis testing, multiple linear regression analysis, relaxed regression analysis, statistical t-tests, F-tests, and coefficient determinations. The output of SPSS is that the results of this study suggest that celebrity endorsement and product quality partially influence purchase decisions, and that brand image may moderate the relationship between celebrity endorsements and purchase decisions. , and that brand image may not moderate the relationship between product quality and product quality. purchase decision. At the same time, through celebrity endorsements and product quality, they jointly or jointly influence purchasing decisions.